Toxicities associated with lymphoma-targeting bispecific antibodies—a review - Doig, Christopher; Yannakou, Costas Kleanthes (Frontiers in Medicine, 2025)
Bispecific antibodies (bsAbs) are an emerging class of directed immunotherapies with established uses in certain hematological malignancies as well as an emerging role in the treatment of solid organ malignancy. These molecules are able to juxtapose T cells (in most cases) with target tumor cells, forming an immunological synapse. bsAbs are under extensive investigation in the treatment of B-cell non-Hodgkin lymphomas, with encouraging results in both the monotherapy and combination therapy settings. In this review we summarize the key toxicities associated with the use of lymphoma-targeting bsAbs: cytokine release syndrome, immune effector cell associated neurotoxicity syndrome, cytopenias, infections and immunosuppression as well as tumor lysis syndrome. While the toxicities are not insignificant, they are typically manageable and justifiable given the unmet medical need, especially in the case of relapsed or refractory disease.